Regulation of cyclin E1 expression in human pluripotent stem cells and derived neural progeny - Rodríguez Varela, Maria Soledad (2018)
Human pluripotent stem cells (hPSCs), including embryonic and induced pluripotent stem cells (hESCs and hiPSCs) show unique cell cycle characteristics, such as a short doubling time due to an abbreviated G1 phase. Whether or not the core cell cycle machinery directly regulates the stemness and/or the differentiation potential of hPSCs remains to be determined. To date, several scenarios describing the atypical cell cycle of hPSCs have been suggested, and therefore there is still controversy over how cyclins, master regulators of the cell cycle, are expressed and regulated. Furthermore, the cell cycle profile and the expression pattern of major cyclins in hESCs-derived neuroprogenitors (NP) have not been studied yet. Therefore, herein we characterized the expression pattern of major cyclins in hPSCs and NP. We determined that all studied cyclins mRNA expression levels fluctuate along cell cycle. Particularly, after a thorough analysis of synchronized cell populations, we observed that cyclin E1 mRNA levels increased sharply in G1/S concomitantly with cyclin E1 protein accumulation in hPSCs and NP. Additionally, we demonstrated that cyclin E1 mRNA expression levels involves the activation of MEK/ERK pathway and the transcription factors c-Myc and E2Fs in hPSCs. Lastly, our results reveal that proteasome mediates the marked down-regulation (degradation) of cyclin E1 protein observed in G2/M by a mechanism that requires a functional CDK2 but not GSK3β activity. Abbreviations: hPSCs: human pluripotent stem cells; hESCs: human embryonic stem cells; hiPSCs: human induced pluripotent stem cells; NP: neuroprogenitors; HF: human foreskin fibroblasts; MEFs: mouse embryonic fibroblasts; iMEFs: irradiated mouse embryonic fibroblasts; CDKs: cyclindependent kinases; CKIs: CDK inhibitors; CNS: central nervous system; Oct-4: Octamer-4; EB: embryoid body; AFP: Alpha-fetoprotein; cTnT: Cardiac Troponin T; MAP-2: microtubule-associated protein; TUJ-1: neuron-specific class III β-tubulin; bFGF: basic fibroblastic growth factor; PI3K: Phosphoinositide 3-kinase; KSR: knock out serum replacement; CM: iMEF conditioned medium; E8: Essential E8 medium.